Pulmonary Rehabilitation and Palliative Care for the Lung Cancer Patient. Issue 5 (October 2015) - Tiep, Brian; Sun, Virginia; Koczywas, Marianna; Kim, Jae; Raz, Dan; Hurria, Arti; Hayter, Jennifer
<x xml:space="preserve">Abstract</x> Pulmonary rehabilitation, as a quality-of-life intervention, has a role to play in palliative care for lung cancer patients. Combining the art and skills of clinical care, physiological, and behavioral tools, pulmonary rehabilitation can serve to rebuild the functional capacity of patients limited by breathlessness and deconditioning. Exercise programs are the primary tool used to restore and rebuild the patient's endurance by challenging the entire pathway of oxygen transport and improving gas exchange. Other tools of pulmonary rehabilitation include breathing retraining, self-management skills, airway clearance techniques, bronchodilation, smoking cessation, and oxygen therapy. Pulmonary rehabilitation is now becoming a part of supportive care for patients undergoing chemotherapy and radiation therapy. The ability to be more active without suffering the consequences of dyspnea on exertion boosts the patient's self-efficacy and allows for an improved quality of life, so that lung cancer patients can participate in their family lives during this therapeutic challenge.